Which Jobs for Which Boys? Party Finance and the Politics of State Job Distribution in Africa. (March 2022) - Sigman, Rachel
Much of the literature on clientelism views the distribution of state jobs in the same way it does other forms of clientelistic exchange: as a mechanism of political mobilization. Despite its prevalence, this perspective does not account for the services that job recipients frequently provide to their political principals beyond the one-time exchange of political support. Drawing on extensive data from Benin and Ghana, including a comprehensive database of minister biographies, surveys of bureaucrats, administrative data, and elite interviews, this article argues that leaders distribute and manage state jobs in ways that enable them to extract and control state money for political financing. Whether incumbent leaders extract state resources themselves, delegate to elite party agents, or co-opt and coerce bureaucrats to divert money to the party shapes which jobs they distribute politically and to whom. The findings suggest that jobs are substantively different from other currencies of clientelistic exchange.